Trabalho colaborativo de Professores nas disciplinas de Matemática e Língua Portuguesa - Menezes, Luís (2012)
The main results obtained in research project Trabalho Colaborativo de Professores nas Disciplinas de Matemática e Língua Portuguesa are presented in this paper. It was developed by four fifth and sixth-year teachers and a university teacher over a period of a year. The project was guided by two great objectives: (i) to increase professional collaboration between teachers of Mathematics and Portuguese; (ii) to promote the development of and integrated vision of the curriculum in these teachers’ students particularly in the disciplines of Mathematics and Portuguese. The data obtained suggest that: teachers took important steps in their professional development, especially in their availability to collaborate with colleagues. The students felt changes in their practices in both disciplines. These changes turned out to be important in creating another vision of the role of each discipline in their learning.